Effect of Mefenamic Acid on Premenstrual Syndrome in Reproductive age Group - Afshan Zaman, Muneeba Sadaf, Maria Tariq, Afnan Rizwan, Uzma Nayyer, Maria Javed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Premenstrual syndrome is a cyclic disorder with symptoms that are severe enough to interfere with some aspect of living. The debilitating symptoms reappear with each cycle, the most common being generalized headache, breast swelling and tenderness, bloating, fatigue, depression and irritability. Aim: To determine the efficacy of mefenamic acid in treatment of premenstrual syndrome women in reproductive age groups. Methods: A quasi experimental study was donein the Department of Obstetrics and Gynecology, Federal Government Services Hospital, Islamabad between November 2020 and April2021. The study was carried out over 75 patients. Mefenamic acid for at least 3 months and followed up for a minimum of 3 months were advised. After follow up the sequel of symptoms and efficacy was noted. Results: Average age of the patients was 26.03±6.27 years. The symptoms of premenstrual syndrome nausea 84%, gastrointestinal tract disturbance 85.3% and headache 80% noted to be the leading symptoms followed by breast tenderness 77.3% and vomiting 74.7%.The efficacy of mefenamic acid in term of relieving of symptoms was observed 70.7%.Statistically significant improvement in symptoms of headache, dysmenorrhea, breast tenderness and mood irritability were noted (p ≤ 0.05). While no clinically significant distinction found among marital status, occupation, education and duration of symptoms improvement (p ≥ 0.05). Practical implication of the study is that the effect of mefenamic acid relieving the symptoms of PMS. Conclusion: The study concluded that mefenamic acid is effective in term of relieving symptoms in patients with premenstrual syndrome. Keywords: Mefenamic acid; Efficacy; Premenstrual syndrome; vomiting.